(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2015)
Abstract This writing presents a research outcome on religious literature of the religious activist at Senior High School (SMA). It aims at explaining student’s reading model towards selected religious readings and identifying affiliation of the understanding on the religious literature. The research is performed by using a textual reception theory which the data is collected through interview and study on the text. This research concludes that students perform a negotiation model reading. The negotiation is carried out in terms of language style. A substance or message with any idea will be interested for them if it is presented by an exciting language style. Meanwhile, there are two styles in the religious literature affiliation, namely moderate style meaning that it corresponds to a mainstream of religious perspective in Indonesia, and another one is based on khilafah ideas that affiliate to a transnational Islamic movement. The second affiliation is more interesting for them since the style is created in an interesting way. Abstrak Tulisan ini menyajikan hasil penelitian tentang literatur keagamaan aktivis Rohani Islam di Sekolah Menengah Atas (SMA). Tujuannya adalah menjelaskan model pembacaan siswa terhadap bacaan keagamaan yang dipilih, dan mengidentifikasi afiliasi pemahaman keagamaan literatur tersebut. Penelitian dilakukan dengan menggunakan teori resepsi teks, yang datadatanya dikumpulkan melalui wawancara dan telaah teks. Penelitian ini menyimpulkan bahwa siswa-siswi melakukan pembacaan model negosiasi. Negosiasi terjadi dalam hal gaya bahasa. Substansi atau pesan dengan ide-ide apapun akan disenangi jika disajikan dengan gaya bahasa yang menarik bagi mereka. Adapun afiliasi literatur keagamaannya ada yang berhaluan moderat dalam arti sesuai dengan arus utama pandangan keislaman di Indonesia, dan ada yang berhaluan ide-ide khilafah yang berafiliasi dengan gerakan Islam transnasional. Afiliasi yang kedua ini yang lebih banyak diminati karena gaya yang menarik bagi mereka.